An insight into direct water injection applied on the hydrogen-enriched rotary engine. (1st May 2023) - Shi, Cheng; Chai, Sen; Wang, Huaiyu; Ji, Changwei; Ge, Yunshan; Di, Liming
Highlights: A method of direct water injection was applied to mitigate knock in Wankel engines. The highest knock propensity occurred at the trailing recess of the rotor chamber. The knock intensity gradually decreased as the amount of water injection increased. Increasing water injection ratios reduce NOx significantly with a penalty in IMEP. Water injection makes H2 -enriched Wankel engines without knocking become possible. Abstract: The attractiveness of direct water injection advantages has made a comeback in the minds of designers due to the potential knock mitigation and lower NOx emissions. The current work established and validated an appropriate 3D model for hydrogen-enriched Wankel engines with direct water injection, and the used CFD simulation was mainly a consideration of combustion and flow phenomena inside the engine and securing the gained knowledge. The determinations of the knock operation and position were investigated, and the intrinsic mechanism of end-gas auto-ignition was clarified. Then, the effects of water injection strategies on knock mitigation and NOx reduction were analyzed in detail. Results showed that the end-gas auto-ignition caused the drastic variation of the local velocity field and the severe pressure oscillation in the vicinity of these regions, which led to knocking combustion. The highest knock propensity occurred at the trailing part of the recess, especially on the opposite side of the intake port. The pressure oscillation of water-enriched schemes was smaller than water-free schemes, and the knock intensity gradually decreased with the advance of water injection timing. When the injection timing was 250°EA, the propensity of end-gas auto-ignition was weakened obviously due to the reduced local temperature and pressure within the rotor chamber, and NOx formation was lower than the other schemes. The local pressure fluctuation was decreased by increasing water addition, whose maximum decrement occurred at the trailing part of the recess. The knock intensity gradually decreased as the amount of water injection increased. When the water injection ratio of 40%, there was no obvious auto-ignition occurrence, and NOx formation reduced significantly at the exhaust moment, which confirmed direct water injection was one of the most promising and effective methods to control knock propensity and NOx emissions simultaneously. In addition, the water droplets of a smaller water injection ratio (10%) scheme spread faster than the water-free scheme after spontaneous combustion, which could reach the fuel surface to present azeotropic phenomena and then enhance the combustion. This result shall give insights into the feasibility of a proper water addition for improving the thermal efficiency of the Wankel engine regime.